The Prognostic Role of Vascular Endothelial Growth Factor-A Expression in Thyroid Carcinomas - Vela-Gaxha Zana; Shahini Labinot; Manxhuka-Kerliu Suzana (Folia Medica, 2019)
Background: Thyroid carcinomas are the most common endocrine tumors – they account for 95% of all endocrine tumors. Thyroid carcinomas are more vascular than normal thyroid tissue. For the tumor to grow and subsequently metastasize it is crucial that it induces angiogenesis. This requires a change in the balance between certain angiogenic factors such as the vascular endothelial growth factor-A (VEGF-A) and the inhibitors of angiogenesis. The aim of this study was to evaluate the role of VEGF-A expression in thyroid carcinomas.